Penguatan Literasi Dan Numersi Anak Melalui Basic Learning - Rahman, Habib Fatkhur; Aditiansyah, Mohammad Abim; Ariyanti, Meika Putri; Fitriyanti, Nafna; Azizah, Binti Khotimatul; Ayodhea, Regita Sheanon; Nisa, Siti Khoirun; Nisa, Alfiatun; Sari, Indri Duhita; Andaryuni, Fitri; sa'diyah, Halimatus; Sa'diyah, Nur Halimatus; et al. (Welfare : Jurnal Pengabdian Masyarakat, 2025)
Students play a crucial role as agents of change through community service activities. One example is the Basic Learning program in Jatirejo Village, which aims to improve children's literacy and numeracy skills. This program utilizes an Asset-Based Community Development (ABCD) approach, encompassing the stages of discovery, dream, design, and destiny, and involves local potential and community support. Activities are routinely conducted with kindergarten, elementary, and junior high school students using creative learning strategies such as animation, educational games, letter cards, and simple teaching aids. The results demonstrate an increase in reading, writing, and arithmetic skills, along with a growing interest in learning and self-confidence. Thus, this program has been proven to contribute to strengthening literacy and numeracy through fun, interactive, and community-based learning in Jatirejo Village.